How Can Law and Policy Reform Shape Human Resource Strategies in Indonesian State Universities Post-Law No. 20 of 2023? - Siti Mursidah; Cahya Wulandari; Moh Khoiruddin; Muhammad Sayuti Hassan; Ricky Dermawan Fauzi (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2024)
Dialectics always arise with the introduction of new policies in laws, and Law No. 20 of 2023 concerning State Civil Servants is no exception. The latest provision in Chapter XIII, Article 65(1), prohibits Personnel Supervisory Officials from appointing Non-Civil Servants to fill civil servant positions, sparking debates on its implications for human resource (HR) management in Indonesian state universities. This study aims to evaluate HR management strategies in state universities, identify obstacles in implementing the law, and propose solutions to optimize its adoption. The research adopts a qualitative method with an analytical descriptive approach. Data was collected through in-depth interviews with HR managers from several public universities in Central Java, supported by a review of relevant documents. The study reveals that while some universities have begun to adopt the provisions of the law, they still face significant challenges, including a lack of professional training and development, complex bureaucratic processes, and budget constraints. Adjusting organizational structures and enhancing staff competencies remain major hurdles. The novelty of this research lies in its focus on the intersection of legal reform and HR strategies in higher education. The urgency is underscored by the immediate need to address inefficiencies and adapt to the law’s mandates. This study contributes by offering actionable recommendations, including increased training and awareness campaigns, simplifying bureaucracy, and expanding budgets for HR development. These insights are essential for policymakers and university administrators to ensure the efficient implementation of Law No. 20 of 2023, ultimately enhancing governance and operational efficiency in Indonesian state universities.